The Influence of Work Experience, Educational Level, and Management Support on the Effectiveness of Accounting Information Systems - I Dewa Ayu Anggitya Pratiwi; Anak Agung Ngurah Agung Kresnandra (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
The effectiveness of accounting information systems (AIS) plays a crucial role in sup-porting the smooth recording, processing, and reporting of reliable and timely finan-cial information. AIS effectiveness is a key concern for cooperative managers in en-hancing operational efficiency and decision-making quality. This study aims to empiri-cally examine how work experience, educational background, and managerial support influence the effectiveness of AIS implementation. The research was conducted at savings and loan cooperatives operating in the South Kuta District. The sampling method used was non-probability sampling with a purposive sampling technique, and data were collected from 54 cooperative employees. Multiple linear regression analysis was employed to process the data. The results indicate that work experience, education level, and managerial support have a positive and significant effect on the effectiveness of AIS implementation. These findings suggest that the higher the em-ployees’ work experience and education, and the stronger the support from manage-ment, the more effective the AIS implementation within the cooperative environ-ment.